The Importance of Emotional Intelligence for Tennis Coaches - Van de Braam, Merlin (ITF Coaching & Sport Science Review, 2013)
The present paper aims to introduce readers to the concept of Emotional Intelligence (EI) and how it may apply to the field of tennis coaching. Recent research will be reviewed that illustrates how EI, within a coaching context, may hold more consequence for career satisfaction and success in comparison to other theories of intelligence such as IQ.